Western Main Road to Staubles, Tetron and Macqueripe - (:unkn) unknown (W.C. Ross and Co. Ltd., Trinidad, 2009)
Shows part of the Western Main Road going west along the north-western peninsula of Trinidad during the colonial period
Black and White; Portrait
Keywords: Postcards; Trinidad and Tobago; Western Main Road; Staubles Bay; Tetron Bay; Macqueripe Bay